Remineralization of enamel subsurface lesions in situ by the use of three commercially available sugar-free gums - MANTON, DAVID J.; WALKER, GLENN D.; CAI, FAN; COCHRANE, NATHAN J.; SHEN, PEIYAN; REYNOLDS, ERIC C. (International journal of paediatric dentistry, 2008)
Background.  Commercially available sugar‐free chewing gums have been claimed to provide oral health benefits. Aim.  The aim of this randomized, double‐blind crossover in situ study was to compare the efficacy of three commercially available sugar‐free chewing gums: Trident White, Orbit, and Orbit Professional, in remineralizing enamel subsurface lesions in situ. Design.  Specimens containing enamel subsurface lesions were sectioned into test and control half‐slabs with the test half‐slabs inserted into removable palatal appliances. For each test chewing period, subjects were randomly allocated one of three test gums. Subjects (n = 10) chewed the randomly allocated gum for a 20‐min period four times per day for 14 days. Each subject chewed all three test gums, with a 7‐day washout period between crossovers. After each 14‐day cycle, test and control half‐slabs were paired, embedded in resin, sectioned, and subjected to microradiography to determine remineralization. Results.  The gum TW produced significantly greater remineralization (18.4 ± 0.9%) than Orbit (8.9 ± 0.5%) and Orbit Professional (10.5 ± 0.9%). Conclusion.  The superior remineralization activity of the TW gum in situ was attributed to the presence of casein phosphopeptide–amorphous calcium phosphate nanocomplexes.